Medical Student Adaption: How the Corellation between Self Efficacy and Educational Enviroment toward Score of Objective Structured Clinical Examination (OSCE) - Megawati, Yuyun Suci; Hartono, .; Randhita, Amandha Boy Timor (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Introduction: The OSCE score, as a component of studentsâ learning performance evaluation, is affected by external and internal factors. An example of an external factor that has an influence is the educational environment, whereas an internal factor that affects OSCE score is self-efficacy. Methods: This study was an observational analytic study, conducted at the Faculty of Medicine UNS. Samples included students of the Faculty of Medicine UNS school year 2013 and 2014. A sample of 189 students was obtained by simple random sampling, and each student was given a questionnaire on self-efficacy using General Self-Efficacy Scale (GSES). Educational environment component was measured with Dundee Ready Education Environment meassure (DREEM). Each component was later interpreted and a comparison was done between school years since they have distinct academic activities. Results: Results from the hypothesis test showed sig of 0,046 which implies a significant correlation between GSES and OSCE scores. Pearson correlation value of 0.186 indicates a weak, positive correlation. Similarly, DREEM and OSCE scores were found to be significantly correlated with sig of 0,000 and Pearson correlation value of 0.375 which also indicates a weak, positive correlation. Conclusion: There is a very weak correlation between self efficacy rate and the Objective Structured Clinical Examination (OSCE) score. Likewise, a weak correlation was also found between the educational environments and Objective Structured Clinical Examination (OSCE) score. Keywords: OSCE score, self-efficacy, educational environmentÂ